2018
DOI: 10.1103/physrevd.98.103018
|View full text |Cite
|
Sign up to set email alerts
|

Gauging fine-tuning

Abstract: We introduce a mathematical framework for quantifying fine-tuning in general physical settings. In particular, we identify two distinct perspectives on fine-tuning, namely, a local and a global perspective -and develop corresponding measures. These measures apply broadly to settings characterized by an arbitrary number of observables whose values are dependent on an arbitrary number of parameters. We illustrate our formalism by quantifying fine-tuning as it arises in two pertinent astrophysical settings: (i) i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…To complete our investigation, we consider an alternative to calculating PBH abundances using Peak Theory, which postulates that PBHs result from peaks in the primordial overdensity field exceeding a threshold value (see Bardeen et al (1986); Green et al (2004) for reviews). It is well known that the PS and Peak Theory do not agree, although previous authors have suggested that Peak Theory is grounded on a firmer theoretical footing, and is more sensitive to the shape of the inflationary power spectrum (Germani & Musco 2019;Kalaja et al 2019;.…”
Section: Peak Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…To complete our investigation, we consider an alternative to calculating PBH abundances using Peak Theory, which postulates that PBHs result from peaks in the primordial overdensity field exceeding a threshold value (see Bardeen et al (1986); Green et al (2004) for reviews). It is well known that the PS and Peak Theory do not agree, although previous authors have suggested that Peak Theory is grounded on a firmer theoretical footing, and is more sensitive to the shape of the inflationary power spectrum (Germani & Musco 2019;Kalaja et al 2019;.…”
Section: Peak Theorymentioning
confidence: 99%
“…If we now assume that PBHs are formed across a spectrum of masses, the monochromatic upper bounds, denoted fmaxitalicmonofalse(Mfalse), must be corrected using procedures such as those previously presented in Azhar & Loeb (2018); Carr et al (2017); Kühnel & Freese (2017); Lehmann et al (2018). These studies have only relatively recently gained traction, but are nevertheless indispensable if PBHs were to be taken as a serious candidate for dark matter and GW sources.…”
Section: Pbh Formation: a Case Studymentioning
confidence: 99%
“…If we now assume that PBHs are formed across a spectrum of masses, the monochromatic upper bounds, denoted f mono max (M ), must be corrected using procedures such as those previously presented in [27][28][29][30]. These studies have only relatively recently gained traction, but are nevertheless indispensable if PBHs were to be taken as a serious candidate for dark matter and GW sources.…”
Section: Observational Constraintsmentioning
confidence: 99%
“…The upshot from these studies is that the corrected upper bound for the total PBH fraction in CDM, f PBH,max , is given by [29]…”
Section: Observational Constraintsmentioning
confidence: 99%
“…II, we describe our schema for an explanation. We introduce a (quantitative) notion of fine-tuning of observables, adapting previous work of ours [in Azhar and Loeb (2018)], and describe how this notion relates to the depth of an explanation. We provide a measure for depth that depends on our description of fine-tuning that can, in principle, be used to compare the depth of explanations across a broad class of physical settings.…”
Section: Introductionmentioning
confidence: 99%